Fatigue behaviour of additively manufactured low alloy steel - Yong, Dylan Ze Quan (Nanyang Technological University, 2024)
In recent years, Additive Manufacturing (AM) has witnessed significant growth, offering numerous advantages over traditional manufacturing methods. Its widespread adoption in major industries like medical, aerospace, automotive, and marine offshore highlights its versatility. As the marine offshore sector evolves to meet diverse needs, there is an increasing demand for intricate components. Despite the common use of structural steels like Low Carbon Steel in shipbuilding due to their excellent mechanical properties, current AM methods still face challenges in optimizing the process and reducing defects like porosities, lack of fusion, inclusions, and unmelted feedstock.